Urinary iodine level assessment during third trimester in a sample of Egyptian pregnant women and its relation to thyroid function - Mohamed, Magda S.; Nasr, Merhan S.; Elhalawany, Salah H.; Tayeh, Salma S.; Abbas, Ahmed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Inadequate intakes of iodine during pregnancy may cause thyroid dysfunctions that adversely affect pregnancy outcomes. Aim of the work was to evaluate the urinary iodine level as a marker of iodine status in a sample of Egyptian pregnant women during 3rd trimester and assess its relation to thyroid functions. Methods: This cross-sectional study was conducted on 100 pregnant females at their 3rd trimester aged (18-35) years. They were divided according to their urinary iodine concentration into 3 groups; Group (I): Pregnant females with deficient iodine (<150 μg/l), Group (II): Pregnant females with adequate iodine (150-249) μg/l, Group (III): pregnant females including who have above requirements (250-499 μg/l), and excessive (≥500 μg/l). TSH, free t4, free t3, Anti-Thyroglobulin (TgAb) and anti-thyroid perioxidase (TPOAb), medium urinary Iodine concentration (UIC) by ELISA and neck U/S were performed to all participants. Results: 18% of the pregnant women in our study had iodine deficiency during 3rd trimester (UIC<150 ug/l) whereas 55% of pregnant women had excess iodine level, and adequate iodine level was observed in 27%. Serum TSH was significantly higher in group I with deficient iodine level (p value<0.01). All pregnant women included at group I were suffering from subclinical hypothyroidism. Serum TSH and thyroid volume were inversely correlated with urinary iodine among pregnant females at 3rd trimester (p value<0.01). Conclusions: Serum TSH and thyroid volume were inversely correlated with urinary iodine level among pregnant females at 3rd trimester.